Development of high performance bituminous mixtures incorporating sugarcane bagasse ash - Wan Noor Hin, Mior Sani; Ungku Hilmy Daniel, Ungku Mohd Arif; Manizawati, Zainal Abidin; Mohamed, Abdullahi Ali; Mohd Hazree, Hashim (Popular Scientist, 2024)
This study investigates the potential of sugarcane bagasse ash as an additive in bituminous mixtures to enhance mechanical properties while promoting sustainability through agricultural waste utilization. Sugarcane bagasse ash was incorporated into 60/70 bitumen at varying contents of 0%, 3%, 5%, and 7%, and its impact on physical, chemical, and mechanical properties was evaluated. The characterization of sugarcane bagasse ash revealed a high silica content (62.43%) and favorable filler properties, contributing to improved performance. The modified binders demonstrated reduced penetration and increased softening points at 3% and 5% sugarcane bagasse ash, indicating enhanced resistance to deformation at high temperatures. The mechanical evaluation showed significant improvements in Marshall stability, stiffness, and indirect tensile strength at 3% and 5% sugarcane bagasse ash, with peak stability (9.965 kN) and indirect tensile strength (753.612 kPa) achieved at 5% and 3% sugarcane bagasse ash, respectively. However, higher sugarcane bagasse ash content (7%) resulted in reduced stability, stiffness, and tensile strength due to excessive voids and weakened cohesion. The correlation analysis revealed strong relationships between stability, density, and abrasion loss, with the optimal performance observed at moderate sugarcane bagasse ash levels. The study concludes that sugarcane bagasse ash is a viable additive for bituminous mixtures, providing improved mechanical performance and sustainability benefits when used at optimal levels of 3%-5%. This research highlights the dual benefits of enhancing bitumen performance and managing agricultural waste, contributing to sustainable construction practices.